Development of back-to-back converter with power transfer control using raspberry Pi - Ahmad Shah, Shahrizan (2015)
It is undeniable that power electronic plays importance role in development of modern technologies. With the aid of power electronics converters its able to manipulate source of power depends on its application. Rapid developments of power electronic device with integration of wide range of controller with intelligence control system have been achieved. In this project, power electronic converters are applied to implement a back-to-back converter with resistive load using Raspberry Pi single board computer as the microcontroller and Hysteresis Band as the controller. MATLAB-Simulink is used to develop the control scheme of the back-to-back converter and incorporate it with Raspberry Pi. Simulation and hardware of back-to-back converter have been developed and the performance of this system is then tested in simulation and hardware for open-loop and closed condition. Interfacing between analog and digital device also has been developed in this project. The output can be controlled according to set point in open-loop and close-loop of simulation analysis.